Intraoperative UBM-guided direct cyclopexy for traumatic cyclodialysis cleft: a four-case series - Fei Wang; Xin Jin; Xiang Chen; Bing Chen; Qing-Li Kong; Bao-Ke Hou (BMC Ophthalmology)
Abstract Purpose To evaluate the feasibility and effectiveness of intraoperative ultrasonic biomicroscopy (UBM)-guided direct cyclopexy for treating traumatic cyclodialysis clefts. Methods Intraoperative UBM-guided direct cyclopexy was performed on a total of four eyes. Prior to the conjunctival incision, UBM evaluation was facilitated with a self-designed eye cup. Scleral flaps were generated according to their respective locations. Before the scleral flaps and conjunctiva were closed, UBM was used to promptly assess the repositioning status. Results 1.UBM-guided direct cyclopexies were performed on four male patients (mean age: 39.7 years). In all instances, the cyclodialysis cleft resulted from blunt ocular trauma, with an average time interval between injury and surgical treatment of 29.5 days. 2. A simple cyclodialysis cleft was observed in two patients. One patient had retinal detachment and subluxation of the lens, and one presented with a shallow anterior chamber, iridodialysis, cataract, vitreous hemorrhage, papilledema, and hypotony maculopathy. 3. Prior to surgery, the mean IOP in all four patients was 7 mmHg (range: 6–9 mmHg), which increased to an average of 16.5 mmHg on postsurgical day three (range: 11–22 mmHg). 4. UBM examination confirmed successful closure of the cleft in all patients. Conclusion During the procedure, UBM-guided direct cyclopexies can accurately assess cyclodialysis cleft repair without being affected by the optical clarity of the refractive media. Preliminary findings demonstrate the feasibility of this approach.